Introduksi Teknologi Pengolahan Kacang Koro Pedang dalam Rangka Inisiasi Sentra Olahannya di Desa Tahai Baru Kalimantan Tengah - Sih Winarti; Wijantri Kusumadati; Hastin Ernawati Nur Chusnul Chotimah; Gusti Irya Ichriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Tahai Baru Village is one of the villages in Maliku Subdistrict, Pulang Pisau Regency, Central Kalimantan, which received funding for the implementation of the koro sword (cangkordang) cultivation activities through the Joint Family Business Program (KUBE) program (PKH). Training and assistance need to be done considering that the Tahai Baru village community does not yet have the knowledge and skills and do not yet know the technology. The purpose of this activity is to increase the knowledge and skills of the people of Tahai Baru Village, Maliku District, Pulang Pisau Regency, in seeing alternative uses of natural resources, especially cangkordang, and increasing community income through processing and packaging of processed cangkordang products. Some approaches are carried out through counseling, training, mentoring, exposure of activities, and evaluating the sustainability and success of the program. The results of the activity showed that the community of Tahai Baru village had knowledge and skills about processing cangkordang and marketing several processed cangkordang products. The implementation of the Mitra Desa Development Program is expected to be able to bring a change in the impact on improving the social welfare of KUBE PKH members and establishing a sustainable partnership between Tahai Baru Village and Palangka Raya University.